Improving weaning strategies for Senegalese sole: effects of body weight and digestive capacity - Engrola, S. (2014)
To optimize Senegalese sole-weaning strategies, three experiments were performed.The first trial tested four weaning strategies with a10mg sole. Artemia-fed sole grew threefold less than fish fed an inert diet. Sudden weaning (abrupt change from Artemia to inert diet) and weaning with co-feeding produced larger sole than did a late weaning treatment; delayed weaning negatively affected ¢sh growth. In the second experiment, the digestive capacity of early-weaned 1, 2 and 4mg sole was investigated. The highest growth was observed in sole weaned at 4mg. Digestive enzyme pro¢les suggest that sole have an adaptation period to inert diets, with reduced feed intake. This adaptation period is inversely proportional to post-larvae weight. The third experiment examined weaning with cofeeding at di¡erent weights (2,5 and11mg).These studies demonstrate that sole of 5^10mg can be weaned, with high survival rates. On the basis of the digestive enzyme pro¢les, the early introductionof inert diets in co-feeding with Artemia seems to affect intestinal processes in smaller postlarvae. This study also suggests that trypsin and alkaline phosphatase may be used as indicators of nutritional status in sole ofo5mg.